Influence of INM Practices on Growth, Yield and Proximate Characters of Baby Corn in Baby Corn (Zea mays L.) – Hyacinth Bean (Lablab purpureus var. typicus) Cropping System - Preetham, R.; Kumar, K. Avil; Srinivas, A.; Rao, A. Manohar; Ramprakash, T. (International Journal of Bio-resource and Stress Management, 2020)
The field experiments were conducted in tropical rainy region of Northern Telangana Zone, India during kharif seasons (July-September) of 2015 and 2016 to study the effect of integrated nutrient management practices on growth and proximate characters of baby corn in Baby corn (Zea mays L.) – Hyacinth bean (Lablab purpureusvar. typicus) cropping system. Experiment was laid in Randomized Block Design for baby corn during kharif 2015 with seven treatments comprised of 100% recommended dose of fertilizers (RDF 150:27:50 N, P and K kg ha-1), 25% N supplemented through farm yard manure or vermicompost + 75% RDF with or without bio-fertilizers Azospirillum and Bacillus megaterium @ 5 kg ha-1 each in addition to control and replicated thrice. Each main treatment was divided into four subplots and the treatments of 100% RDF (20-22 N, P kgha-1) and 75% RDF with or without Bradyrhizobium @ 500 g ha-1 (seed treatment) were imposed for hyacinth bean in rabi season and data of kharif 2016 was analyzed in split plot design. Application of 25% N through vermicompost in conjunction with 75% RDF and bio-fertilizers to baby corn during kharif resulted in significantly higher plant height, leaf area index, root volume, cob plant -1, cob length, cob girth, cob width, cob weight, cob yield, stover yield, protein content and significantly lower fiber content over rest of treatments during 2015 and 2016. 100% RDF along with seed treatment with Bradyrhizobium to hyacinth bean during preceding rabi resulted in significantly higher growth, yield attributes, yield and proximate characters of baby corn in the succeeding kharif 2016 over rest of the treatments of 100% RDF, 75% RDF with or without Bradyrhizobium seed treatment.